Pengaruh Varians Anggaran Pendapatan, Varians Anggaran Belanja, dan Ukuran Pemerintah Daerah terhadap Kinerja Keuangan - Frety Suci Tiara Hati; Kartika Rachma Sari; Sopiyan AR (Economic Reviews Journal, 2025)
This study aims to analyze the effect of revenue budget variance, expenditure budget variance, and local government size on the financial performance of district/city governments in South Sumatra Province. Financial performance is measured using an efficiency ratio that describes how optimally local governments manage their budgets. The data used are secondary data obtained from the Regional Government Financial Reports (LKPD) of 17 districts/cities in South Sumatra Province. The analysis method used in this study is panel data regression with the help of the Eviews 12 application. The results of the study indicate that revenue budget variance has a significant negative effect on regional financial performance, which means that the greater the deviation between the budget and revenue realization, the lower the efficiency of financial performance. Conversely, expenditure budget variance has a significant positive effect, which indicates that spending realization that is smaller than the budget can reflect the efficiency of fund use. The size of the local government also has a significant positive effect on financial performance, which indicates that the greater the total assets owned by the region, the more efficient its financial management. These findings are expected to be a consideration for local governments in preparing and realizing budgets more appropriately and efficiently.